Fast computation of scalar optical diffraction pattern for pixelated spatial light modulators (In English) [Pikselli uzamsal işik kipleyicileri için skalar optik kirinim deseninin hizli hesaplanmasi (TÜRKÇE)] - (:unkn) unknown (IEEE Computer Society, 2014)
Spatial light modulators can be used for having dynamic three dimensional images. Diffraction pattern of three dimensional objects can be used for driving those imaging devices. Diffraction patterns have to be calculated rapidly to form dynamic three dimensional images. Furthermore, pixelated structure of the spatial light modulators have to be taken into account in the diffraction pattern calculation to improve the quality of the reconstructed objects. The proposed method for calculating diffraction patterns not only takes into account the pixelated structure of the spatial light modulator to obtain more accurate results, but also provides fast calculation of the diffraction pattern. The proposed method employs a lookup table which is formed by 469 pre-computed vectors and the computation time of diffraction pattern can be decreased significantly compared to standard diffraction pattern calculation method. The proposed method can be run in parallel, hence further reduction in calculation time can be achieved and even the diffraction pattern of a three dimensional object which is formed by 3144 points can be calculated within 80msec when the algorithm is run in parallel on a graphics processing unit. © 2014 IEEE.
Keywords: Computer-Generated Holography; Graphical Processing Unit; Look-Up Table; Parallel Processing; Spatial Light Modulator